Detection of acute toxicity of aflatoxin B1 to human hepatocytes in vitro and in vivo using chimeric mice with humanized livers - Ishida, Yuji; Yamasaki, Chihiro; Iwanari, Hiroko; Yamashita, Hisahiko; Ogawa, Yuko; Yanagi, Ami; Furukawa, Suzue; Kojima, Yuha; Chayama, Kazuaki; Kamiie, Junichi; Tateno, Chise (PLOS ONE, 2020)
Aflatoxin B1 (AFB1), a mycotoxin, is acutely hepatotoxic to many animals including humans. However, there are marked interspecies differences in sensitivity to AFB1-induced toxicity depending on bioactivation by cytochrome P450s (CYPs). In the present study, we examined the applicability of chimeric mice with humanized livers and derived fresh human hepatocytes for in vivo and vitro studies on AFB1 cytotoxicity to human hepatocytes. Chimeric mice with highly humanized livers and SCID mice received daily injections of vehicle (corn oil), AFB1 (3 mg/kg), and carbon tetrachloride (50 mg/kg) for 2 days. Histological analysis revealed that AFB1 promoted hepatocyte vacuolation and inflammatory cell infiltration in the area containing human hepatocytes. A novel human alanine aminotransferase 1 specific enzyme-linked immunosorbent assay demonstrated the acute toxicity of AFB1 to human hepatocytes in the chimeric mouse livers. The sensitivity of cultured fresh human hepatocytes isolated from the humanized liver mice for AFB1 cytotoxicity was comparable to that of primary human hepatocytes. Long-term exposure to AFB1 (6 or 14 days) produced a more severe cytotoxicity. The half-maximal lethal concentration was 10 times lower in the 2-week treatment than after 2 days of exposure. Lastly, the significant reduction of AFB1 cytotoxicity by a pan-CYP inhibitor or transfection with CYP3A4 specific siRNA clearly suggested that bioactivation of AFB1 catalyzed by CYPs was essential for AFB1 cytotoxicity to the human hepatocytes in our mouse model. Collectively, our results implicate the humanized liver mice and derived fresh human hepatocytes are useful models for studies of AFB1 cytotoxicity to human hepatocytes.